"CoviSainik program" - A novel public private partnership initiative in the control of COVID-19 in rural India - Rupali Sabale; Gajanan Velhal; Vinayak Sonawane; Shilpi Gupta (Wolters Kluwer Medknow Publications, 2023)
Background: "CoviSainik Program" was implemented in collaboration with the Ambuja Cement Foundation and Community Medicine Department in rural districts of eight states of India from May to December 2021 to create a cadre of volunteers. The aim of the present paper is to describe the program and evaluate it so that the findings can be the guiding tool for policymakers to replicate a similar program. Material and Method: A cross-sectional, mixed-method - concurrent study design was adopted to evaluate the program for its short-term outcomes such as gain in the basic knowledge of COVID-19 amongst master trainers and their feedback and program output viz - the proportion of volunteers trained and their profile by census sampling. Motivational factors, experiences of volunteers, and outcomes of COVID-19 work in their villages were explored by purposive with maximum diversity sampling with 62 online in-depth interviews and 8 online focus group discussions (FGDs). Results: There was a statistically significant difference in the pre-test (12.8 ± 5.6) and post-test (25.9 ± 9.3) scores of the Master Training Program evaluation test. Out of 6534 trained volunteers, 5901 worked as volunteers, and amongst those, 47.1%, 35.1%, and 17.8% worked for ≤3 months, 3 to 6 months, and ≥6 months, respectively, in their villages. The major themes generated for motivational factors to join the program were altruism, savior nature, generating awareness, and concern for others. The major outcomes generated by trained volunteers COVID-19 vaccination were in raising awareness on COVID-19 appropriate behavior and early identification of COVID-19 cases in their villages. Conclusion: The "CoviSainik Program" was successful in creating cadres of trained volunteers.